1993
DOI: 10.1007/bf00302729
|View full text |Cite
|
Sign up to set email alerts
|

Dentin sialoprotein: biosynthesis and developmental appearance in rat tooth germs in comparison with amelogenins, osteocalcin and colagen type-I

Abstract: A non-collagenous protein, extracted from rat incisor dentin, is a dentin sialoprotein (DSP). We examined immunohistochemically the developmental appearance and tissue distribution of DSP in 1 to 3-day-old rat molar and incisor tooth germs. The earliest staining for DSP was observed in newly differentiated odontoblasts. In more advanced stages, immunostaining for DSP gradually increased in pre-dentin, odontoblasts and dentin, and appeared in many cells of the dental papilla. In early stages of development befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 34 publications
7
50
1
1
Order By: Relevance
“…Snead et al (1984) isolated RNA from first molars of mice of various ages and found greatest hybridization to a radiolabeled amelogenin probe at birth and in 1 day postnatal mice. Results from immunohistochemistry experiments using anti-amelogenin antibodies have suggested that expression begins in pre-ameloblasts in rat molars (Inai et al, 1991;Bronckers et al, 1993). We, however, have not found evidence for expression in any part of the tooth that does not have some mineralized matrix present.…”
Section: Transgenic Mice Specifically Express Pgalactosidase Activitycontrasting
confidence: 72%
“…Snead et al (1984) isolated RNA from first molars of mice of various ages and found greatest hybridization to a radiolabeled amelogenin probe at birth and in 1 day postnatal mice. Results from immunohistochemistry experiments using anti-amelogenin antibodies have suggested that expression begins in pre-ameloblasts in rat molars (Inai et al, 1991;Bronckers et al, 1993). We, however, have not found evidence for expression in any part of the tooth that does not have some mineralized matrix present.…”
Section: Transgenic Mice Specifically Express Pgalactosidase Activitycontrasting
confidence: 72%
“…However, differentiated odontoblasts could not be identified by a unique phenotypic marker; a combination of markers such as Dsp, Dpp, Dmp1, and nestin has been applied to identify these cells (18). Dspp and/or its cleaved products Dsp and Dpp are believed to be tooth-specific (11), although they are also expressed in preameloblasts (6,8,10,15,43,44). Recent studies have shown the expression of Dspp in bone (41,42), cementum (3), and some non-mineralized tissues (2,37,38), while its expression in non-dental tissues is lower than that in dentin.…”
mentioning
confidence: 99%
“…Another major dentin NCP, dentin sialoprotein (DSP), is a 53-kDa sialic acid-rich glycoprotein that accounts for 5-8% of the dentin extracellular matrix [Butler et al, 1992]. DSP was reported to be synthesized by odontoblasts, some pulp cells and preameloblasts [Butler et al, 1992;Bronckers et al, 1993]. Immunohistochemical studies showed that DSP was present in predentin and dentin but not in enamel, bone, muscle or cartilage [Butler et al, 1992;Bronckers et al, 1993].…”
mentioning
confidence: 99%